ANALYSIS OF PHYSICO CHEMICAL PROPERTIES OF LOW CALORIE HERBAL FLAVOURED MILK* - T.R. Pugazhenthi; S. Jothylingam (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Herbal flavoured milk was prepared by incorporating Aloe vera pulp extract at different concentrations viz. 3, 5 and 7 per cent.  Based on the sensory evaluation, herbal flavoured milk with 5 per cent Aloe vera pulp extract was found to be the best. Different low calorie herbal flavoured milk were prepared using artificial sweeteners like aspartame and sucralose at different levels of sugar replacement and stored at 5oC up to 5 days for further analysis. Based on the sensory evaluation, dietetic herbal flavoured milk up to 75 per cent replacement of sugar with aspartame and 100 per cent replacement of sugar with sucralose were found to be ideal. Among the various physico chemical properties analysed in dietetic herbal flavoured milk, the mean pH and titratable acidity were within the normal range. When the level of artificial sweeteners was increased to replace the sugar, the specific gravity, viscosity, SNF and total solids content decreased. There was no significant difference (P > 0.05) between the control and various treatments with regard to fat, lactose, total ash, minerals like calcium, phosphorus, sodium, potassium and iron contents. On the contrary, there was a highly significant (P < 0.01) difference in SNF and total solids content.